2000
DOI: 10.1002/(sici)1097-0142(20000315)88:6<1317::aid-cncr7>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-macrophage-colony stimulating factor in combination immunotherapy for patients with metastatic renal cell carcinoma

Abstract: BACKGROUND The aim of this study was to determine the response rates and toxicity of two regimens containing granulocyte‐macrophage–colony stimulating factor (GM‐CSF) in combination with interleukin‐2 (IL‐2) in the treatment of patients with metastatic renal cell carcinoma. METHODS Therapy given in the first trial (Trial 1) consisted of irradiation to the primary tumor or metastatic site, followed by GM‐CSF 100 μg/day administered subcutaneously (sc) for 2 weeks and IL‐2 11 × 106 IU sc 4 days per week for 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The aim for EBRT was, for some patients, pain palliation; for others, we hoped to obtain a synergy with the immunotherapy by increasing the antigenicity of the radiated tumor cells. 20 Although our study was not carried out in a randomized fashion, by reviewing retrospectively our results from a heterogeneous sample of patients, our data confirm the absence of efficacy of EBRT as an adjuvant treatment to IL-2 immunotherapy in MRCC and are in agreement with those of Redman et al 41 and Ryan et al, 42 though others have reported encouraging results. 43 Following our first observation, 10 some phase I studies with intralymphatic rIL-2 have been initiated.…”
Section: Discussionsupporting
confidence: 88%
“…The aim for EBRT was, for some patients, pain palliation; for others, we hoped to obtain a synergy with the immunotherapy by increasing the antigenicity of the radiated tumor cells. 20 Although our study was not carried out in a randomized fashion, by reviewing retrospectively our results from a heterogeneous sample of patients, our data confirm the absence of efficacy of EBRT as an adjuvant treatment to IL-2 immunotherapy in MRCC and are in agreement with those of Redman et al 41 and Ryan et al, 42 though others have reported encouraging results. 43 Following our first observation, 10 some phase I studies with intralymphatic rIL-2 have been initiated.…”
Section: Discussionsupporting
confidence: 88%
“…Granulocyte macrophage colony-stimulating factor (GM-CSF) is known as a potent hematopoietic growth factor for granulocyte and macrophage expansion and is considered to play a critical role in anti-tumor responses by dendritic cells (DCs) maturation and T cell proliferation and activation [ 8 ]. However, clinical trials in metastatic RCC (mRCC) using GM-CSF as single-agent or combined with either interleukine-2 (IL-2) or interferon-α (IFN-α) have failed to show anti-tumor effect [ 9 11 ]. Although RCC vaccination studies using GM-CSF as immune adjuvant have shown promising results, it is not clear whether this cytokine is indispensable for the clinical improvement [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%